1988
DOI: 10.1128/aac.32.12.1848
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of cephalosporins and resistance caused by decreased affinity for penicillin-binding proteins in Bacteroides fragilis

Abstract: The susceptibilities of 52 clinical isolates of Bacteroides fragilis to five monoanionic cephalosporins were examined. Cefoperazone showed the highest antibacterial activity, followed by ceftezole, cefazolin, cefamandole, and cephalothin. There were two groups of resistant strains: one group (ca. 15%), of which B. fragilis G-232 was a typical sample, was resistant to ceftezole (MIC, 100 micrograms/ml), cefazolin (MIC, 100 micrograms/ml), and cephalothin (MIC, 200 micrograms/ml) but not cefoperazone (MIC, 6.25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 33 publications
1
26
1
Order By: Relevance
“…In case of B. fragilis group species, the discrepancy in OMP profiles between the laboratory mutants and their parent strains was not observed in the studies done by Piddock and Wise [15], Wexler and Halebian [18], and Yotsuji et al [19]. In the present study, we found that the 2 mutants lost an ∼37-kDa OMP that was expressed in the parent strains and the type strain.…”
Section: Discussioncontrasting
confidence: 71%
“…In case of B. fragilis group species, the discrepancy in OMP profiles between the laboratory mutants and their parent strains was not observed in the studies done by Piddock and Wise [15], Wexler and Halebian [18], and Yotsuji et al [19]. In the present study, we found that the 2 mutants lost an ∼37-kDa OMP that was expressed in the parent strains and the type strain.…”
Section: Discussioncontrasting
confidence: 71%
“…Doxycycline acts on the bacterial 30S ribosomal subunit (19), while ceftriaxone can generally be described as having beta-lactam activity (20). Although previous clinical studies showed that doxycycline can be as effective as third-generation cephalosporin antibiotics like ceftriaxone (21,22), recent in vitro work suggests that doxycycline may not be as effective as ceftriaxone against stationaryphase bacteria (23).…”
mentioning
confidence: 86%
“…In that study, decreased susceptibility to cefoxitin could be correlated with decreased affinity of either penicillin-binding protein 1 (PBP-1) or PBP-2, while three isolates also had outer membrane protein changes, with a 49,000-to 50,000-molecular-weight band apparently absent. A strain of B. fragilis in which reduced affinity for PBP-3 was apparently responsible for resistance to ceftezole, cefazolin, and cephalothin has been studied by Yotsuji and coworkers (127). Wexler and Halebian (114) isolated a cefoxitin-resistant laboratory mutant and the cefoxitin-susceptible revertant and showed that decreased susceptibility to cefoxitin could be correlated with changes in the PBP-1 complex.…”
Section: Issues That Require Further Investigation Endpoint Definitionmentioning
confidence: 99%